Salbutamol benefits children with congenital myasthenic syndrome due to DOK7 mutations. - Burke, G; Hiscock, A; Klein, A; Niks, E; Main, M; Manzur, A; Ng, J; de Vile, C; Muntoni, F; Beeson, D; Robb, S (2013)
Congenital myasthenic syndromes due to DOK7 mutations cause fatigable limb girdle weakness. Treatment with ephedrine improves muscle strength. Salbutamol, a β(2)-adrenergic receptor agonist with fewer side effects and more readily available, has been effective in adult and anecdotal childhood cases. This study reports the effects of salbutamol on motor function in childhood DOK7 congenital myasthenic syndrome. Nine children (age range 5.9-15.1years) were treated with oral salbutamol, 2-4mg TDS. The effect on timed tests of motor function, pre- and up to 28months post-treatment, was audited retrospectively. All 9 reported functional benefit within 1month, with progressive improvement to a plateau at 12-18months. Within the first month, all 3 non-ambulant children resumed walking with assistance. Although improvements were seen in some timed tests (timed 10m, arm raise time, 6min walk time) this did not fully reflect the observed functional benefits in daily living activities. No major side effects were reported. We conclude that oral salbutamol treatment significantly improves strength in children with DOK7 congenital myasthenic syndrome and is well tolerated. Outcome measures need to be refined further, both to accurately reflect functional abilities in children and to document progress and treatment response.